pengaruh Pengaruh Kualitas Layanan Home Care Terhadap Kepuasan Dan Kepercayaan Pasien Di Kecamatan Panakkukang Kota Makassar - Azis, Irma Kusuma; Palu, Basri; Ahri, Reza Aril (Window of Health : Jurnal Kesehatan, 2018)
Home health care is an existing program that needs to be developed, as it has become a community need. The Home Care Program was established because people have been complaining about the difficulty of accessing quick and accessible public health services to all corners of the city, including areas that do not have equitable access. The purpose of this study is to analyze the effect of service quality on patient satisfaction and trust in Districts Panakkukang City of Makassar. Research design using survey approach and using explanation (level of explanation. While the type of research is quantitative research to explain the effect of quality of Home Care services consisting of: reliability, responsiveness, empathy, assurance, and physical appearance of patient satisfaction and trust in 4 Puskesmas in Districts Panakkukang City of Makassar. The results of this study indicate that: After the statistical test, it was found that the Quality of Home Care Service had an effect on Patient Satisfaction (significance 0,008 <0,05), Quality of Home Care Service Influence to Patient Trust (significance 0,001 <0,05), Patient Satisfaction Patient Trust (significance 0.000 <0.05). This study suggests the need for socialization of Home Care, training for Home Care team and the addition of medical personnel.